Injecting drugs as a matter of care: Analyzing care work and action programs in risk management - Jukka Törrönen; Josefin Månsson; Eva Samuelsson; Jessica Storbjörk (SSM: Qualitative Research in Health)
In this article, we analyze the care work employed by people who inject drugs to counter risks in their life situations and make their drug use safer. Injecting drugs is associated with numerous health and social risks, such as overdose, the use of used and shared equipment, and getting caught by the police. We approach descriptions of injection events as narratives of care. Participants (N = 32) were recruited for semi-structured interviews primarily from the Stockholm Needle and Syringe Exchange Program between August 2022 and March 2023. The sample is heterogeneous in terms of age, gender, drug use, and social situation. The interviews were analyzed using actor-network theory, asking what kind of care work and ‘action programs’ strengthen or weaken participants' capacities for safer injection events and what kinds allow risks – or antiprograms – to enter the event. We identified four different action programs based on home or public settings. They all aimed to increase capacities for safe drug use, but two of them were more vulnerable to risks. Their success depended on the type of actors they could recruit for care work, the risks they were targeting, and how well they coordinated actors to work together to minimize risks. The analysis highlights the scope, strengths, and limitations of care work in relation to material, social, political, and institutional actors, as well as the importance of access to proper resources such as a home, stable income, and a healthy body.